2012
DOI: 10.1159/000339749
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and Limitations of Sequential Serum Tryptase for the Diagnosis of Anaphylaxis in 102 Patients

Abstract: Background: The diagnosis of anaphylaxis is based on clinical history since no reliable biological marker is currently available to confirm the diagnosis. Objective: It was the aim of this study to determine sequential serum tryptase concentrations during anaphylaxis and to evaluate its potential as a diagnostic marker. Methods: We performed a prospective study including patients with acute anaphylaxis (according to the National Institute of Allergy and Infectious Disease/Food Allergy and Anaphylaxis Network c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 63 publications
4
120
0
5
Order By: Relevance
“…In a prospective study in adults, serum total tryptase concentrations were measured sequentially 1-2, 4-6, and 12-24 h after the onset of anaphylaxis symptoms and at baseline (follow-up). In 62% of the patients, initial tryptase levels were elevated (mean 19.3 ± 15.4 μg/l) with positive correlation between grades of severity and tryptase levels (p < 0.001, r = 0.49) [48]. …”
Section: Clinical Diagnosismentioning
confidence: 99%
“…In a prospective study in adults, serum total tryptase concentrations were measured sequentially 1-2, 4-6, and 12-24 h after the onset of anaphylaxis symptoms and at baseline (follow-up). In 62% of the patients, initial tryptase levels were elevated (mean 19.3 ± 15.4 μg/l) with positive correlation between grades of severity and tryptase levels (p < 0.001, r = 0.49) [48]. …”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Baseline measurements are useful for allowing comparison to acute measurements, therefore enhancing diagnostic capacity. Although anaphylactic reactions to intravenous drugs have been shown to elicit greater increases in tryptase levels than oral triggers such as foods [13], our observational study has not identified significant differences in sBT levels and the types of triggers involved, but sBT levels were significantly higher among patients with more severe anaphylaxis. Our results are in keeping with those of Sahiner et al [23], who showed the relevance of sBT levels in predicting the risk of anaphylaxis in food allergy: a cutoff of 5.7 ng/mL was associated with a 50% probability of moderate-severe anaphylaxis.…”
Section: Discussionmentioning
confidence: 64%
“…The use of tryptase measurement for the diagnosis of anaphylaxis is well established [13, 15, 22]. However, one single acute measurement of the tryptase level may not be decisive to establish the correct diagnosis of anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Normal tryptase levels do not exclude the possibility of anaphylaxis, which can remain normal in 36% of patients who had clinically defined anaphylaxis. 31 A possible explanation is anaphylaxis attributed to local release of tryptase (e.g. in laryngeal oedema), which may not be sufficient to increase the total serum tryptase concentration; alternatively, there may be a greater participation of basophils than mast cells in the mechanism of anaphylaxis in some situations.…”
Section: Norwaymentioning
confidence: 99%